Zombie Terrorism in an Age of Global Gothic. Issue 2 (1st November 2015) - Unknown
Abstract : With reference to films such as The Terror Experiment (2010) and Osombie (2012), this paper explores the figure of the zombie terrorist, a collectively othered group that is visually identifiable as 'not us' and can be slaughtered with impunity. In cinematic treatments, the zombie terrorist operates within a collectivity of zombies, erasing the possibility of individuality when the transformation from human to zombie takes place. The zombie terrorist signifies otherness in relation to selfhood, and is characterised by a mind/body split. Emerging from the grave in the archetypal zombie primal scene, this reanimated corpse is undead in its animate corporeality coupled with a loss of all mental faculties. The erasure of individual identity and memory along with broader human characteristics such as empathy or willpower coincides with the zombie terrorist' s physical movement and action.